Employee’s Well-Being and Job Performance A Case Study in Government-Affiliated Entities - Rozie Zurfi Chandra; Ramon Zamora; Lukmanul Hakim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Before and under COVID-19, government-affiliated firms kept Indonesia's economy stable and under control. Indonesia and other countries have been struck hard by COVID-19, which has accelerated governmental and commercial sector digitisation. In the face of the pandemic's rapid digitalisation, SOEs must expand and improve to accomplish their goals. This research will examine how technostress, perceived organisational support (POS), total reward systems (TRS), and work-life balance (WLB) affect job performance through employee well-being. State-owned enterprise personnel will be studied. This quantitative study examines the dependent variable's direct and indirect impacts using Structural Equation Modelling (SEM). The majority of research participants are from 263 government-affiliated entities. The study found that employee well-being modulates the association between perceived organisational support and work performance. The results demonstrate that SOEs must involve all generations, especially millennials and Gen Z, to improve job performance. The paper states that employee well-being is the complete mediator between the factors and job performance. Organisations should continually encourage employees and make them feel valued. This is crucial for Generation Y and Z, who will run the company.